Halal Food Regulations in Malaysia: Concept and Compliance - Md Ismail, Che Thalbi; A. Rahman, Aspalella; Abdullah, Nor Anita (Serials Publications, 2017)
Islam demands Muslims to opt the good and the best in every facet of life including for food consumption. Generally, everything is halal to eat. However, there are certain prohibited food provided by the Syariah law. For this purpose, Islam has outlined the rules and regulations for food consumption. Further, this permitted food must not only be halal, but also toyyiban. This article highlights the rules and regulations pertaining to the halal and prohibited food. This article then elaborates the element of ‘toyyiban’, another requirement beside ‘halal’. Finally, it explains whether the concept of halal under the Malaysian law is in conformity with these Islamic rules and regulations. To achieve this objective, a qualitative analysis will be made to the relevant rules. This article concluded that the concept of halal applied by the Malaysia authority is in line with the Syariah rules. However, to ensure that the food is toyyiban also needs an extra awareness by each of muslim individual